Analysis of the Role of Market Levies in Increasing Regional Revenue in Indonesia - Nabila Ramadhani; Lailatul Sangadah; Riski Amalia; Putri Aulia; Adila Nurhasana; Natasha Az-Zahra; Firmansyah Firmansyah (Jurnal Ekonomi & Bisnis, 2025)
Market levies play a strategic role in strengthening Local Own-Source Revenue and supporting regional fiscal independence. This study analyzes the effectiveness, contribution, and factors influencing the management of market levies based on research findings from eleven regions, including Jombang Regency, Prabumulih City, Takalar Regency, Manggarai Regency, Sikka Regency, Blora Regency, South East of Maluku Regency, Balangan Regency, Wajo Regency, Pandaan City, and Banjarbaru City. The method employed is content analysis of quantitative and qualitative data obtained from each location. The findings indicate that regions with high effectiveness levels, such as Regency Jombang and Prabumulih City, have shown a positive impact on PAD. Conversely, regions with low effectiveness, such as Sikka Regency, have yet to achieve optimal results. Supporting factors include good management, accurate data collection, trader participation, and the use of digital technology, while inhibiting factors consist of low trader awareness, weak supervision, and inaccurate market potential data.